An Assessment on the Constitution of Nepal 2015 - Gautam, Dilli Raj (Journal of Political Science, 2020)
This paper aims to critically examine the major features, strengths and weaknesses of the present constitution of Nepal (2015) applying the fundamental instruments of constitutionalism as a measuring rod. The Constitutional discourse of Nepal moved through seven Constitutions so far. It can be better linked to a laboratory of constitutional experiments of the constitutions of 1948, 1951, 1959, 1962, 1990, 2007, and 2015. The present constitution of Nepal (2015) was promulgated with the motive of political and social transformation strengthening democracy, human rights, ensuring equality, liberties and social justice to the people. In order to explore the features, strengths and weaknesses of the constitutions available texts and other materials on the constitution were collected first and then the content analysis method was followed to explore the major features, strengths and weaknesses of the constitution. Based on the analysis, dynamism and flexibility, comprehensive catalogue of fundamental rights and inclusiveness and proportional representation were found as the major features. Incorporation of adequate economic, social and cultural rights including group rights empowerment of women and minorities inclusiveness and proportional representation are the major attributes of the present constitution. In spite of popular acceptance of the people's verdict and wider inclusion of progressive arrangement the constitution still conceives some weaknesses on vague and clumsiness of preamble, disparity on citizenship issues and constituency delineations, enlistment of ambitious and unenforceable rights and composition of politically shadowed judiciary.